Social distance of class leaders from primary and secondary school students and their parents - Milošević Aleksandra M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
The quality of interpersonal relationships between participants in the educational process (class teachers, students, parents) affects the creation of a favourable socio-emotional climate in and out of the classroom, and is also a significant factor of integration or disintegration of the collective, good or bad interpersonal relationships, satisfaction or dissatisfaction, success or failure achieved by students. In general, it always has a positive effect on the development of students' behaviour, and it depends on the conditions under which a class was formed, the way the class is managed, the position that students have in the class, their mutual relations and students' readiness for appropriate cooperation. With this paper, we explored the social distance that the class teacher sets in relation to students and their parents as an important prerequisite for a qualitative, open and productive cooperation among the actors of the educational process. The sample consisted of teachers in the role of class teachers, students and their parents from 36 primary and secondary schools in the Zlatibor district. The results of this research indicate that class teachers in primary and secondary schools generally have a close relationship with students and parents, although a more direct cooperation is achieved by class teachers in primary schools than in secondary ones. This confirms a more intensive educational function of primary school, as opposed to a more dominant educational function of secondary school and thus a more dynamic, complex, open and direct work of class teachers in primary school with students and parents.